The Dynamics of Rotor with Rubbing - Jerzy T. Sawicki; Joe Padovan; Rabih Al-Khatib (International Journal of Rotating Machinery)
This paper presents the description of some phenomena associated with dynamic behavior of rotors interacting with stationary components. Numerical simulations show rotor vibration spectrum rich in subharmonic, quasi-periodic, and chaotic vibrations. The nonlinear calculation techniques are applied to demonstrate the changes of the vibration patterns for different operating conditions. Some conclusions are discussed with regard to unique characteristics of rub-induced rotor response, initial conditions, as well as appropriate ranges of system parameters. Of special interest are the changes in the apparent nonlinearity of the system dynamics as rubs are induced at different rotor speeds. In particular, starting with 2nd order sub/superharmonics, which are symptomatic of quadratic nonlinearity, progressively higher order polynomial behavior is excited, i.e., cubic, giving rise to 3rd order sub/superharmonics. As the speed is transitioned between such apparent nonlinearities, chaotic like behavior is induced because of the lack of whole or rational tone tuning between the apparent system frequency and the external source noise. The cause of such behavior will be discussed in detail along with the results of several parametric studies.